Population differentiation supports multiple human-mediated introductions of the transatlantic exotic sponge Paraleucilla magna (Porifera, Calcarea) - Cavalcanti, F.F.; Padua, A.; Cunha, H.; Halasz, M.; Nikolić, V.; Barreto, S.; Klautau, M. (Hydrobiologia, 2020)
Paraleucilla magna was the first sponge recognised as alien in the Atlantic. It was first registered in Rio de Janeiro (Brazil) and soon became very abundant in the southeastern and southern coasts of Brazil and also in the Mediterranean. Its origin is still unknown but recurrent introductions seem to have occurred in the Mediterranean. In this study, we used genetic markers (microsatellites) to test if Brazilian and Adriatic populations share a single source or if multiple introductions occurred in both regions. We also compared the genetic composition of populations established almost 30 years ago (Brazil) with a recently founded population (Adriatic—less than 10 years). Populations of P. magna were sampled in four localities across 900 km in the Southwestern Atlantic (Brazilian coast) and in one locality in the Adriatic (Croatian coast). Our results suggest the presence of five genetically distinct populations possibly originated by multiple human-mediated introductions from different sources and show that the putative most recently established population is genetically more diverse.